2013
DOI: 10.1111/febs.12366
|View full text |Cite
|
Sign up to set email alerts
|

A novel phospholipase B from Streptomyces sp. NA684 – purification, characterization, gene cloning, extracellular production and prediction of the catalytic residues

Abstract: A novel metal ion-independent phospholipase B (PLB 684 ) from Streptomyces sp. strain NA684 was purified 264-fold from the culture supernatant with 2.85% recovery (6330 UÁmg protein À1 ). The enzyme functions as a monomer with a molecular mass of 38.9 kDa. Maximum activity was found at pH 8.4 and 50°C. The substrate specificity was in the order: phosphatidylcholine ≥ phosphatidic acid ≥ lysophosphatidylcholine > phosphatidylserine > phosphatidylinositol > phosphatidylglycerol. The enzyme did not hydrolyze phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…In particular, a secreted PLA 2 produced by Streptomyces violaceoruber A-2688 isolated from a soil sample, was described as the first PLA 2 identified in prokaryote (Sugiyama et al, 2002; Takemori et al, 2012). Similarly, a PLA 1 and a phospholipase B have also been reported in the Streptomyces genus (Sugimori, Kano & Matsumoto, 2012; Matsumoto et al, 2013). Some authors have also reported the presence of lipases in actinomycete strains (Sztajer, Maliszewska & Wieczorek, 1988) while others did not observe the production of lipolytic enzymes (Basha et al, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…In particular, a secreted PLA 2 produced by Streptomyces violaceoruber A-2688 isolated from a soil sample, was described as the first PLA 2 identified in prokaryote (Sugiyama et al, 2002; Takemori et al, 2012). Similarly, a PLA 1 and a phospholipase B have also been reported in the Streptomyces genus (Sugimori, Kano & Matsumoto, 2012; Matsumoto et al, 2013). Some authors have also reported the presence of lipases in actinomycete strains (Sztajer, Maliszewska & Wieczorek, 1988) while others did not observe the production of lipolytic enzymes (Basha et al, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…The optimal pH for the rPLB enzyme was 5.5 (Figure 2b), which is more acidic than the optimum pH for the PLB from Streptomyces sp. (pH 8.4) [23]. In addition, rPLB retained more than 35% of its maximum activity over a broad pH range of 4.5-8.5 (Figure 2), whereas other PLBs display no or low activity at pH values ranging from 5.0-9.0 [6,8,10,11].…”
Section: Characterisation Of Rplbmentioning
confidence: 98%
“…Doi and Nojima reported that lysophospholipase (Phospholipase B) activity was inhibited by 10 mM Fe +3 , and Al +3 . He also reported that Ca +2 also affects the phospholipase B activity and stability [4,44]. Divalent metal ions affects phospholipids by forming complexes and affects the hydration of phosphate group [4,[45][46][47] (p > 0.05).…”
Section: Effect Of Chemicals On the Activity And Stability Of Tmplb1mentioning
confidence: 99%
“…They showed high preference for substrate from lysophospholipids to diacylphospholipids and hydrolyzes diacylphospholipids without forming lysophospholipids. Some of the phospholipase B enzyme having lysophospholipase-transacylase activity which transfers free fatty acids to lysophospholipids and forms diacylphospholipid [4].…”
Section: Introductionmentioning
confidence: 99%